Proud humility: paradoxes of self-representation in Huguenot memoir - Baker, N (2023)
This thesis makes a contribution to early modern trauma theory and life-writing studies. I use memoirs written by French Protestants after the 1685 Revocation of the Edict of Nantes to explore the emotional impact of migration in the late seventeenth and early eighteenth centuries. In the past, some Huguenot historians have taken such ‘ego-documents’ as entirely veridical and factual accounts, whereas I engage with the metaphors and intertextual references employed by the writers. The present work can thus be situated within the growing field of Huguenot memoir scholarship. The central argument of this thesis is that memoir-writing offered refugees a space in which they could explore challenging moments in their pasts. In order to address the variety of post-Revocation experiences encountered by early modern Huguenots, each chapter of this thesis deals with a distinct ‘case study’ of sorts. I first look at writing by women who were imprisoned following initial unsuccessful attempts to escape France. I then focus on how galley slavery was depicted by Protestants who had close contact with its horrors. Finally, I explore memoirs whose contents concentrate on the difficulties of adapting to new cultures. Each of the authors whose works are examined in this thesis had their own personal concerns, but across the range of writings, some common strategies emerge for dealing with common issues. I engage with archival material and contemporary publications from the Grand Siècle to develop as full as possible an understanding of the authors’ worldviews, arguing that religious doctrine could be a source of both solace and stress. Throughout, I highlight what life-writing can reveal about inner, emotional worlds. I thus establish narrative as an important tool for Huguenots dealing with trauma in the early modern period.